Conidiobolomicose, artrite encefalite caprina e coccidiose em pequenos ruminantes no semiárido brasileiro - Aguiar, Gildeni Maria Nascimento de (2015)
Was performed a clinical-epidemiological studies of conidiobolomycosis diseases of sheep, arthritis encephalitis and eimeriosis goats in order to contribute to the determination of risk factors and supporting the establishment of effective control strategies for these diseases. To understand he conidiobolomycosis we performed a case-control study in properties in the states of Paraíba and Rio Grande do Norte and analyzed 23 outbreaks of the disease. The identified risk factors were grazing in pond margins, grazing for a long time; presence of plant matter in the margins and increased grazing pressure. With this work, it was concluded that the combination of factors such as constant grazing in wetlands with decomposed plant material and soil rich in organic matter exposes the animals to infection Conidiobolus spp. and predisposes to outbreaks. Presented a case of the a goat Saanen, was sent to the Veterinary Hospital of the Federal University of Campina Grande, for clinical signs of motor incoordination for seven days. Laboratory, serological examinations and the necropsy determined the diagnosis of neurological form of CAE. Based on this diagnosis, there were visits to properties where information was obtained on the housing system, food and health management. All herd animals underwent clinical and serological examination for CAE using the immunodiffusion in agar gel, in two stages. The predominant clinical sign in animals with neurological signs was the ataxia of the pelvic members. In the first examination 60% (45/75) of the animals were seropositive, including 26.6% (12/45) had signs of arthritis. We observed an incidence rate of 19,69 % (13/66). In addition to the confirmation of a case of leukoencephalomyelitis, considered a more rare form of CAE, this work identified the main difficulties of the producers institute recommended control measures. In the experiment concerning the dynamics ofinfection by Eimeria spp. in different rearing systems and the effect of infection on the performance of the kids were formed two experimental groups, and group 1 (extensive system) and 2 (intensive system). Parasitological examination and weighing of the animals were carried out for 12 weeks. In group 1, the seventh and tenth week there was a negative correlation between OPG and weight gain. In group 2 the week of less weight gain identified an increased elimination of oocysts. The infection with Eimeria spp. occurred in all animal herds, but there were no clinical signs. The highest average excretion in group 2 shows that in intensive systems the animals are more exposed to contamination. To minimize the occurrenceof the illness should avoid stresses associated with high stocking density, low power quality and failure in hygiene installations.